Shear failure in reinforced concrete members without transverse reinforcement: analysis of model error of NBR6118:2014 - Barros,Vinicius Paes de (2021)
Abstract This article presents an analysis of NBR6118:2014 models used to determine the one-way shear strength in reinforced concrete members without transversal reinforcement. The study compares model predictions with 751 experimental results, taken from the 2015 ACI-DAfStb database and from Quach. Model errors are quantified. Mean values observed are around unity, indicating models with no bias, but coefficients of variation are large. Model error trends are identified with respect to cross-section depth and longitudinal reinforcement rate. In elements with low rate of longitudinal reinforcement and/or large cross-section depths, the normative models provide results with low safety. This shows the need for revision of the normative models. By means of non-linear regression analysis, two correction terms are proposed to consider the longitudinal reinforcement rate and the size effect (decrease in shear strength with increase in section depth). With the proposed corrections, the observed trends are eliminated, and the design equation becomes more accurate with respect to cross-section shear.